Pengaruh Hedonic Experience & Opinion Leadership Terhadap Quality Content Yang Dirasakan Dari Konten Pada Aplikasi Tiktok - Nisa, Choirul; Vandayuli Riorini, Sri (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to analyze the extent to which the quality of influencer content on TikTok affects followers' belief that influencers can provide Opinion Leadership. TikTok is one of the social media that is increasingly used by consumers to collect information as a basis for decision making. Influencers on social media like TikTok are considered role models and influencers for their followers, especially when it comes to fashion, lifestyle, photography, and travel. Previous research has shown that the quality of influencer content and affective factors such as influencer-follower proximity, homophily, and emotional contagion influence favorable follower responses to influencer publications. Therefore, this study will focus on the quantity and quality of influencer posts as an important factor to increase the influence capacity and trust of followers towards influencers as opinion leaders on TikTok. This research is about the influence of Hedonic Experience and Opinion Leadership on Quality Content on the TikTok application, and based on the results of descriptive statistics, it can be concluded that TikTok application users consider that the application can provide a pleasant experience, offer interesting short videos that show creative ideas from influencers, and like short video content created by influencers.